1998
DOI: 10.1063/1.121495
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of bulk and interfacial properties of Ba0.5Sr0.5TiO3 thin film capacitors

Abstract: Articles you may be interested inEffects of in-plane compressive stress on electrical properties of ( Ba,Sr)TiO 3 thin film capacitors prepared by on-and off-axis rf magnetron sputtering Epitaxial growth and planar dielectric properties of compositionally graded ( Ba 1−x Sr x ) TiO 3 thin films prepared by pulsed-laser deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 4 publications
2
38
0
Order By: Relevance
“…In order to clarify the interfacial problem, the frequency dependence of complex dielectric constant for some compounds in PZT and (Bi 2 O 2 ) 2+ (A m−1 B m O 3m+1 ) 2− systems has been studied. A remarkable low frequency dielectric dispersion below T c was observed in thin film capacitors of PZT [18], BST [19][20][21], Sr x Bi y Ta 2 O 9 (SBT) [8], Bi 2 Ti 2 O 7 [9], and Bi 4 Ti 3 O 12 [10]. It has been shown that this phenomenon greatly affects the electrical properties of the capacitors.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In order to clarify the interfacial problem, the frequency dependence of complex dielectric constant for some compounds in PZT and (Bi 2 O 2 ) 2+ (A m−1 B m O 3m+1 ) 2− systems has been studied. A remarkable low frequency dielectric dispersion below T c was observed in thin film capacitors of PZT [18], BST [19][20][21], Sr x Bi y Ta 2 O 9 (SBT) [8], Bi 2 Ti 2 O 7 [9], and Bi 4 Ti 3 O 12 [10]. It has been shown that this phenomenon greatly affects the electrical properties of the capacitors.…”
Section: Introductionmentioning
confidence: 95%
“…They proposed that the BLT thin film exhibits a fatigue-free characteristic and large remanent polarization. However, even if the BLT thin film is free from fatigue and imprint to simple Pt electrodes, they can also see an interfacial (electrode/bulk) problem similar to Pb(Zr x Ti 1−x ) O 3 (PZT) [18] and (Ba, Sr)TiO 3 (BST) [19][20][21] thin films. In order to clarify the interfacial problem, the frequency dependence of complex dielectric constant for some compounds in PZT and (Bi 2 O 2 ) 2+ (A m−1 B m O 3m+1 ) 2− systems has been studied.…”
Section: Introductionmentioning
confidence: 97%
“…A higher dielectric permittivity at lower frequency region is expected due to the increasing polarization contribution ͑consisting of interface, dipolar, ionic/atomic, and electronic͒ at the lower frequencies. 20 However, compared with the BLF film, permittivity of BST/BLF/BST structure exhibited a relatively weak frequency dependence. The dielectric constant of the trilayer structures is almost uniform at ϳ 180 throughout the measurement frequency.…”
mentioning
confidence: 99%
“…In order to clarify the interfacial problem, the frequency dependence of complex dielectric constant for some compounds in PZT and (Bi 2 O 2 ) 2+ (A m−1 B m O 3m+1 ) 2− systems has been studied. A remarkable low frequency dielectric dispersion below T c was observed in thin film capacitors of PZT [18], BST [19][20][21], Sr x Bi y Ta 2 O 9 (SBT) [8], Bi 2 Ti 2 O 7 [9], and Bi 4 Ti 3 O 12 [10]. It has been shown that this phenomenon greatly affects the electrical properties of the capacitors.…”
Section: Introductionmentioning
confidence: 95%
“…: +82 55 740 1241; fax: +82 55 740 1240. (BST) [19][20][21] thin films. In order to clarify the interfacial problem, the frequency dependence of complex dielectric constant for some compounds in PZT and (Bi 2 O 2 ) 2+ (A m−1 B m O 3m+1 ) 2− systems has been studied.…”
Section: Introductionmentioning
confidence: 99%